Combating administrative and financial corruption and its impact on supporting and strengthening sustainable development in the thought of Imam Ali (PBUH) - Dr. Diaa Awad Dhahab Al-Khuwailidi (Journal of College of Education, 2025)
Sustainable development is one of the priorities of state building, and one of the most important matters that Islamic law and other heavenly and positive laws have paid attention to, and the wise have called for it in their theories; because through it, man lives in safety and security, if the construction is correct according to the standards that God Almighty wanted, and which reached us through the messengers and prophets, especially the Seal of them, Muhammad (PBUH).Administrative and financial corruption stands as an obstacle to sustainable development, and is a destructive tool for building the state, so wherever this disease occurs in a state, its fate is destruction, ruin and failure, and the state does not return to its renaissance except by fighting this deadly disease.The research aims to demonstrate the thought of Imam Ali (PBUH) in sustainable development through his fight against administrative and financial corruption, due to its great importance in building the state that God, His Messenger, and the righteous among His servants call for, the state that is built on the basis of justice and equality among people in rights and duties, according to the divine standards and scales, which have been allocated to each person with a right; because God does not wrong anyone, as stated in the Holy Quran.
Keywords: sustainable development, State building , Imam Ali thought